Analytical and finite element analysis of shape memory polymer for use in lumbar total disc replacement. (October 2021) - Kiyani, Saeed; Taheri-Behrooz, Fathollah; Asadi, Amir
Abstract: One-piece bearing is the latest type of total disc replacement (TDR) design that is used for the treatment of lumbar degenerative disc disease (DDD). Due to the unique properties of the shape memory polymers (SMPs), such as self-healing, shape-memory, adhesion control, and self-deployable ability, they may be a good candidate for the core of such a design. The purpose of the present study is to use an analytical method combined with a numerical analysis (finite element analysis (FEA)) to determine the mechanical responses of an SMP intervertebral disc (IVD) model, under pure torsion (axial rotation) and pure compression, two loading conditions to which natural intervertebral discs (IVDs) are subjected in vivo. We considered the SMP IVD model to be positioned at L4-L5 because most cases of lumbar DDD are reported at this segment. For the analytical method, an appropriate constitutive equation for an SMP was determined and, then, an analytical solution for the torsional response of a circular SMP IVD model, in a full cycle of stress-free strain recovery, was derived. The developed equations were implemented in finite element modeling to determine responses of the IVD disc model under pure torsion. Additionally, responses of the SMC IVD model, under a compressive load, and different conditions were determined. The analytical and FEA results were compared to experimental results give in the literature for intact lumbar spine segments as the core in a one-piece lumbar TDR. Based on this study, we suggest that SMPs can be used for TDR, as they are strong enough to bear the torsional and compressive loads that IVD is subjected through its life.